Topical transport of hydrophilic compounds using water-in-oil nanoemulsions - Wu, Huailiang; Ramachandran, Chandrasekharan; Weiner, Norman D; Roessler, Blake J (International journal of pharmaceutics, 2001)
A variety of water-in-oil nanoemulsions were prepared using sorbitan monooleate (Span®80), polyoxyethylene 20 sorbitan monooleate (Tween®80), olive oil and water. The nanoemulsions were tested for their ability to facilitate transport of a model hydrophilic solute, inulin, across hairless and hairy mouse skin and hairy rat skin following topical in vitro application. The transport of inulin incorporated in water-in-oil nanoemulsions was found to be significantly higher (5- to 15-fold) than that obtained with micellar dispersions or aqueous controls. The rate and extent of inulin transport across hairy mouse skin was found to be highly dependent on the hydrophile–lipophile balance (HLB) of the surfactant mixture in the nanoemulsion. Nanoemuslions prepared using mixtures with lower HLB exhibited significantly higher rate and extent of transport. It was also found that nanoemulsion-mediated transport was independent of molecular size of the hydrophilic solute and the nature of the aqueous phase. More importantly, transport of inulin from nanoemulsions was independent of animal skin characteristics such as stratum corneum thickness and follicle-type. The combined results suggest that water-in-oil nanoemulsions that are compatible with the lipophilic sebum environment of the hair follicle facilitate efficient transport of incorporated hydrophilic solutes and imply that such transport is predominantly transfollicular in nature.